Tackling Antimicrobial Resistance in the Shadow of COVID-19 - Ami Patel (American Society for Microbiology, 2021)
ABSTRACT The coronavirus disease 2019 (COVID-19) pandemic is a challenge for ongoing efforts to combat antimicrobial-resistant (AMR) bacterial infections. As we learn more about COVID-19 disease and drug stewardship evolves, there is likely to be a lasting impact of increased use of antimicrobial agents and antibiotics, as well as a lack of consistent access to health care across many populations. Sexually transmitted infections have been underreported during the pandemic and are often caused by some of the most drug-resistant pathogens. In their recent article in mBio, Parzych et al. (E. M. Parzych, S. Gulati, B. Zheng, M. A. Bah, et al., mBio 12:e00242-21, 2021, https://doi.org/10.1128/mBio.00242-21) focus on protection against Neisseria gonorrhoeae infection via in vivo delivery of an antigonococcal DNA-encoded antibody that has been modified for increased complement activation. Nucleic acid approaches are highly adaptable and could be tremendously beneficial for personalized strategies to combat AMR pathogens.